Emenda Constitucional nº. 95/2016: Impactos no Financiamento do Gasto Social do Governo Federal (2017-2022) - Santos, Franciele Quevedo dos (2024)
The subject of this dissertation is Constitutional Amendment No. 95/2016 and the financing of social spending by the federal government from 2017 to 2022. The central question of this research is: what are the impacts of Constitutional Amendment 95/2016 on the financing of social spending (social policies)? The hypothesis guiding our study is that the implementation of EC 95 reduced the resources allocated to social spending, restricted rights, agavated social inequality and increased the resources allocated to rentier capital, mainly through the payment of interest, charges and amortization of the public debt in the period analyzed. The general objective of this research is to analyze the impacts of Constitutional Amendment (CA) No. 95/2016 on the financing of social spending from 2017 to 2022. In order to define which expenses are considered social spending, which is the object of analysis in this work, we took as a reference the classification of the Union's functional expenses systematized by the National Institute of Pedagogical Studies Anísio Teixeira (INEP, 2020). According to INEP, the following areas are considered social spending (social policies): Public Security, Social Assistance, Social Security, Health, Labor, Education, Culture, Citizenship Rights, Urban Planning, Housing, Sanitation, Agrarian Organization and Sports and Leisure. Constitutional Amendment No. 95/2016 instituted a New Fiscal Regime within the Union's Fiscal and Social Security Budgets, freezing primary (nonfinancial) spending for twenty years: 2017-2036. This amendment, in practice, was in force until 2022 and, as a mechanism to contain primary spending, was replaced by Complementary Law 200/2023, which instituted the so-called “Sustainable Fiscal Regime”, starting in 2024. The research is a documentary and bibliographical analysis, with the empirical source being data collected from the Integrated Budget and Planning System (SIOP), made available by the Ministry of Finance. In analyzing the evolution of the federal government's social spending, we took the amounts paid by the Federal Government as a reference. These amounts were adjusted by the Broad National Consumer Price Index (IPCA) for January 2024. The time frame for the analysis is 2017, the year EC 95/2016 comes into force, to 2022, the last year the constitutional amendment is in force. During the period in which EC 95/2016 was in force, the federal government's social spending, in proportional terms, was reduced when compared to total federal spending. In 2017, social spending represented 40.69% of total federal spending and in 2022 it fell to 34.05%.